HUBUNGAN ANTARA PENGETAHUAN DENGAN SIKAP IBU TERHADAP METODE KONTRASEPSI JANGKA PANJANG - Indah Dewi Ridawati; Frida Nurmala (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2021)
This research was reffered to the increasing of population matters and government program in applying long-term contraception method as the solution. For dealing with that matters we need to have a good knowledge about family planning and contraception tools used by acceptor in selecting contraception tools. Since the knowledge has been domain in shaping one’s behavior, and the acceptors could used long-term method. This study aimed to establish the relationship between knowledge and mothers’ attitudes toward long term contraception in village population. This study employed descriptive correlational research design and involved 100 mothers by simple random sampling in Bojong Village, Cianjur District, Indonesia. Data were analysed using chi square. The results showed that there is not significant correlation between the two variables (p=0,64). We cannot say that there is a relationship between knowledge they had and score participants presenting on the scale of attitudes.